Food insecurity response and severity to changes in integrated household dependency ratio in Maiduguri Metropolis, Borno State, Nigeria - Ali, I. M; Jibrin, S.A.; Bulama, Y. M; Mamadi, A. A. (ADAN JOURNAL OF AGRICULTURE, 2025)
This study analyzed food insecurity response and severity to changes in integrated household dependency ratio in Maiduguri Metropolis, Borno State, Nigeria. It covered 15 and five peripheral wards of Maiduguri Metropolitan and Jere LGAs respectively. A two-stage sampling procedure was adopted to draw respondents for the study; Purposive selection of ten large concentrations of integrated household wards and proportionate random selection of 376 integrated households. Both primary and secondary data were used for the study. Descriptive and inferential statistics were employed to analyze the data collected. The descriptive statistics used were frequency tables, percentages and mean while inferential statistics included food insecurity response model (FIRM). The integrated household food insecurity response was positive with a coefficient of 0.307, 0.895 and 1.507 for mild, moderate and severe food insecure households respectively.